2020
DOI: 10.21848/asr.190107
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Depressive Symptoms in the Elderly with Hearing Impairment

Abstract: Purpose: The purpose of this study was to examine factors associated with depressive symptoms in the elderly with hearing impairment.Methods: We studied 23 hearing-impaired elderly persons aged 60 years or older. The participants underwent audiometric, neuropsychological, and depression assessments. Neuropsychological tests were subsumed in specific cognitive domains (general cognition, semantic memory, processing speed, executive function). The short version of the geriatric depression scale was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study similarly also found patients' subjective hearing handicap level to be a predictor of .60 Adjusted R 2 .58 social isolation. These results indicate that a significant subjective hearing handicap in daily life increases social isolation and can lead to the development of psychological issues such as depression, [22] which indicates an urgent need for measures to mitigate age-related hearing loss patients' communication difficulties in various environments. In this study, experience using hearing aids was a predictor of social isolation, and social isolation was higher among those who did not have experience using hearing aids than among those who did.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study similarly also found patients' subjective hearing handicap level to be a predictor of .60 Adjusted R 2 .58 social isolation. These results indicate that a significant subjective hearing handicap in daily life increases social isolation and can lead to the development of psychological issues such as depression, [22] which indicates an urgent need for measures to mitigate age-related hearing loss patients' communication difficulties in various environments. In this study, experience using hearing aids was a predictor of social isolation, and social isolation was higher among those who did not have experience using hearing aids than among those who did.…”
Section: Discussionmentioning
confidence: 99%
“…The proper use of hearing aids can compensate for hearing loss as well as prevent further deterioration of patients' ability to hear. [22,23] Therefore, the use of hearing aids is expected to substantially reduce the degree to which older adults with hearing loss experience social isolation. This study has limited applicability for generalizing the findings since it was conducted with patients at a single university hospital only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations